Seleucid Piety: Antiochus VII and the Siege of Jerusalem - Abakumov, Arkady Alekseevich (Античный мир и археология, 2017)
This article is dedicated to the famous siege of Jerusalem by Seleucid king Antiochus VII Sidetes, who, according to Josephus Flavius, had expressed benevolence and respect to the Jews and their religion. The author considers this  “lenience” and “piety” as display of Sidetes’ desire to imitate his ancestor Antiochus The Great who was also respected by the Jews as benevolent ruler.